Ovine footrot in Southern Portugal: detection of Dichelobacter nodosus and Fusobacterium necrophorum in sheep with different lesion scores. - Albuquerque, Catarina (2022)
The Mediterranean climate region of Alentejo in the Southern of Portugal is an important sheep production centre but little is known about the presence and characteristics of Dichelobacter nodosus in association with Fusobacterium necrophorum in the different footrot lesion scores. DNA from 261 interdigital biopsy samples, taken from 14 footrot affected flocks and from three non-affected flocks, were analysed for the presence of D. nodosus and F. necrophorum by real-time PCR. Both virulence and serogroup were determined for 132 and 53 D. nodosus positive biopsy samples, respectively. The co-infection with both bacteria was the commonest epidemiological finding associated with a greater disease severity. There was a statistically significant association (p =  0.002) between footrot-affected flocks and the presence of D. nodosus. Most D. nodosus positive samples were virulent (96.2%) and belonged to serogroup B (90%).